Micro‐tomographic characterization of composite recycled glass‐silicone foams for applications in civil engineering. Issue 21 (13th November 2019) - Calabrese, Luigi; Scalici, Tommaso; Khaskhoussi, Amani; Proverbio, Edoardo; Valenza, Antonino
ABSTRACT: Noninvasive X‐ray micro‐computed tomography was applied for a complete quantitative and qualitative analysis of the cellular structure of composite foams constituted by a silicone matrix and a glass production waste filler. Composite foams with different glass filler weight content in the range 0–80% were synthesized and characterized. The tomographic analysis was employed in order to assess the structural heterogeneities, void fraction values, and bubble size distribution for all composite foams. The 3D micro‐CT images analysis, performed at different cross‐sections, highlighted heterogeneous cell growth or more elongated cells in the case of low and high filler content foams, respectively. Batch with 60% of glass filler was identified as a composite foam with effective void fraction values and relatively uniform spheroidal cellular structure (average sphericity 0.723 and diameter 0.107 mm). © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48718. Abstract :